2018
DOI: 10.1891/0886-6708.vv-d-17-00015
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Myths in Police Reports: A Directed Content Analysis

Abstract: Although much has changed in social and criminal justice system responses to intimate partner violence (IPV) since public awareness campaigns began in the 1970s, stigmatization around IPV offense and victimization remains a barrier to victims obtaining available assistance, including those offered by police forces. Unfortunately, stigma is often perpetuated by mythology about the crime, its offenders, its victims, and overarching gender norms. Since IPV cases are managed under the auspices of the criminal just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Results demonstrated that when the DV incident involved a physical altercation between the victim and suspect, the odds of service referral increased by three times as compared to DV cases involving only emotional and/or psychological abuse, reiterating prior research (Kernic & Bonomi, 2007). This finding likely reflects police perceptions of urgency and severity, where physical DV is often perceived as more legitimate, credible, and serious when compared to abuse that does not produce demonstrable physical injury (Dichter et al, 2011;Eigenberg et al, 2012;El Sayed et al, 2020;Twis et al, 2018). El Sayed et al (2020), for instance, recently found that nearly 500 officers from nine Southern police agencies indicated that evidence of physical trauma was one of the most important factors influencing perceptions of victim credibility.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Results demonstrated that when the DV incident involved a physical altercation between the victim and suspect, the odds of service referral increased by three times as compared to DV cases involving only emotional and/or psychological abuse, reiterating prior research (Kernic & Bonomi, 2007). This finding likely reflects police perceptions of urgency and severity, where physical DV is often perceived as more legitimate, credible, and serious when compared to abuse that does not produce demonstrable physical injury (Dichter et al, 2011;Eigenberg et al, 2012;El Sayed et al, 2020;Twis et al, 2018). El Sayed et al (2020), for instance, recently found that nearly 500 officers from nine Southern police agencies indicated that evidence of physical trauma was one of the most important factors influencing perceptions of victim credibility.…”
Section: Discussionmentioning
confidence: 55%
“…Physical altercation captured incidents of DV that involved a physical attack as opposed to electronic or verbal threats/abuse and was coded as a binary variable (No = 0, Yes = 1). Suspect weapon use, victim injury, suspects use of threats to kill, and stalking are often used to reflect the severity of partner abuse (Dichter et al, 2011;Garza et al, 2020;Twis et al, 2018). Weapon use, which excluded bodily force, was captured through explicit, affirmative mention that the suspect threatened or used a weapon in the incident and was coded as a binary variable (No = 0, Yes = 1).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Therefore, the police members were not able to make a clear distinction among these. These incidents were thus overlooked as the police members relied on their own discretion to make decisions (Saxton et al, 2021; Twis et al, 2018). As such, no arrests were made for emotional and sexual violence, only referrals to the magistrates’ offices.…”
Section: Discussionmentioning
confidence: 99%
“…Myths and stereotypes among the police relating to gender roles also contribute. The location and types of IPV incidents, victims belonging to a minority racial/ethnic group, and having a history of IPV have also been reported (Fedina et al, 2018; Saxton et al, 2021; Serrano-Montilla et al, 2021; Twis et al, 2018).…”
Section: Ipv and Policingmentioning
confidence: 99%
“…Research has also shown some biases of police officers, for example in reports related to intimate partner violence (Twis et al, 2018). A study conducted in Hong Kong compared the injury grading in police reports with the trauma records of a regional hospital (Tsui et al, 2009).…”
Section: The Reports Might Be Biasedmentioning
confidence: 99%